Relatório de estágio curricular realizado na Câmara Municipal de Lisboa - Almeida, Andreia Neves de (2015)
The experience of an internship is always considered an experience that should be enriching, a first contact with the employment world. The intention is to build a bridge between the theory and practice - applying what has been learnt throughout the course. Therefore, it was started a new learning phase that seeks to take advantage and obtain experiences useful for a professional life based in efficiency and efficacy. The curricular internship was carried out within the Masters in Public Law and held by Faculdade de Direito da Universidade Nova de Lisboa (FDUNL)(Law School Of University New Of Lisbon) in the Câmara Municipal de Lisboa (CML) (Lisbon's Town Hall), in the Departamento de Política de Solos e Valorização Patrimonial (DPSVP) (Soil Politics and Patrimonial Valuation Department) of the Direção Municipal de Planeamento, Reabilitação e Gestão Urbanística (Municipal Direction of Planning, Rehabilitation and Urban Management) between September and December 2013. Throughout this internship, several activities within the DPSVP were developed. In an early stage, there was a presentation of the organic structure of Lisbon's Town Hall, and the Department where I was going to do the internship, and its competencies. Therefore I acquired key concepts and researched jurisprudence and legislation needed to the analysis and understanding of the activities done in the internship. In a second stage, it was done the analysis and understanding of the division into lots administrative procedures, as well as the solving of the problems occurred throughout that analysis. Besides that, there was the need to help preparing some procedural acts to be applied regarding the Department competencies, namely within the alienation, procurement, encumbrance and rental of immovable assets owned by the Municipality of Lisbon.